2016
DOI: 10.11648/j.crj.20160401.13
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Polycythemia Vera in Campus Teaching Hospital of Lome - Togo

Abstract: The annual prevalence of polycythemia vera is about 2.16 new cases. The average age of patients was 46, 7 years with ranges from 31 to 65 years. There were 9 men and 4 women. The most frequent factor of finding was the fortuitous ones (23%). Most clinical signs represented were headache (69.2%), skin érythroses (53.8%) and paresthesia (30.8%). The average value of hemoglobin, hematocrit, the number of white blood cells and platelets in our patients with polycythemia who had positive JAK2V617F was respectively:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Several studies have shown polycythemia to be more common in males than females with a ratio of 2:1. 8 , 23 , 24 The gender disparity in the occurrence of polycythemia vera was partly shown to be due to gender influence on JAK2 (V617F) allele burden and this may produce phenotypic differences in the disease. 25 Palandri et al, 5 in a review on the gender effect of polycythemia vera, acknowledging the effects of gender-specific diagnostic thresholds underscored the influence of gender on the clinical presentation, symptom burden, and pathogenesis of polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown polycythemia to be more common in males than females with a ratio of 2:1. 8 , 23 , 24 The gender disparity in the occurrence of polycythemia vera was partly shown to be due to gender influence on JAK2 (V617F) allele burden and this may produce phenotypic differences in the disease. 25 Palandri et al, 5 in a review on the gender effect of polycythemia vera, acknowledging the effects of gender-specific diagnostic thresholds underscored the influence of gender on the clinical presentation, symptom burden, and pathogenesis of polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms that are commonly reported at presentation include headache, dizziness, pruritus, numbness, epigastric discomfort, bleeding, tiredness, visual disturbances, tinnitus, and night sweats. 8 , 11 , 23 , 24 , 26 Headache has been found as the most common presenting symptom. 8 , 23 , 24 In this study, headache was found to be the most common complaint at presentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations